True hermaphroditism with sex cord tumor with annular tubules (SCTAT): a rare case report and review of the literature - Suhua Shi; Ming Tang; Wuan Li; Haixing Wu; Yinhua Liu; Yonghong Luo; Huafeng Ding (BMC, 2022)
Abstract Background True hermaphroditism is a rare condition. It is defined as the presence of both testicular and ovarian tissues in the same individual. Sex cord tumour with annular tubules (SCTAT) is a rare stromal tumour of the sex cord that occurs mostly in the ovaries. Case presentation A 16-year-old girl presented to the gynaecology department with primary amenorrhea. Gynaecological examination revealed an enlarged clitoris that looked like a small penis. The chromosome karyotype was chimaera. The postoperative pathology confirmed true hermaphroditism with SCTAT. The patient underwent hormonal replacement after an operation and had no evidence of recurrence for 6 months. Conclusion Cases of true hermaphroditism with SCTAT are extremely rare conditions. Surgery and hormonal replacement are important for improving the prognosis of such patients.